2015
DOI: 10.1186/s12936-015-0670-y
|View full text |Cite
|
Sign up to set email alerts
|

Plasmodium vivax malaria at households: spatial clustering and risk factors in a low endemicity urban area of the northwestern Peruvian coast

Abstract: BackgroundPeru has presented a decreasing malaria trend during the last decade, particularly in areas on northwestern coast; however, a limited number of cases continues to be reported yearly mainly in malaria hotspots.MethodsA two-phase study was conducted to identify spatial and temporal clusters of incident Plasmodium vivax malaria, as well as to determine risk factors associated with households (HH) presenting P. vivax malaria episodes in an urban area of the northwestern Peruvian Coast from June 2008 to M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
33
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 34 publications
(46 reference statements)
4
33
0
3
Order By: Relevance
“…albimanus 53. The most affected people live in peri-urban localities in close proximity to irrigated fields and irrigation canals which enable anopheline mosquitoes to propagate and survive 20,53. Although houses in those localities have complete walls (closed houses), they are mainly made of poor materials that do not exclude mosquitoes.…”
Section: Peruvian P Vivax-endemic Regionsmentioning
confidence: 99%
“…albimanus 53. The most affected people live in peri-urban localities in close proximity to irrigated fields and irrigation canals which enable anopheline mosquitoes to propagate and survive 20,53. Although houses in those localities have complete walls (closed houses), they are mainly made of poor materials that do not exclude mosquitoes.…”
Section: Peruvian P Vivax-endemic Regionsmentioning
confidence: 99%
“…Outside West Africa, other plasmodial species have also shown spatial clustering. For example, Rosas-Aguirre et al have reported that the prevalence of Plasmodium vivax infection is highly heterogeneous on the northwestern coast of Peru [11].…”
Section: Introductionmentioning
confidence: 99%
“…Using different malaria transmission variables at the micro-epidemiological level, maps and models have been produced to guide National Control Programmes in Africa and Southeast Asia 12,[17][18][19][20][21][22] . By contrast in the Americas, where the dynamics of malaria transmission is different from Africa and Southeast Asia due to differences in vector bionomics, social conditions or parasite genetic structure among others, relatively few studies have attempted to identify transmission heterogeneity, whether using epidemiological data 23 , serological tools 24,25 or assessing the effect of ecological differences on malaria transmission 26 .…”
mentioning
confidence: 99%